2004
DOI: 10.1038/sj.leu.2403348
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of flow cytometry and polymerase chain reaction for the detection of minimal residual disease in childhood acute lymphoblastic leukemia

Abstract: Minimal residual disease (MRD) is an independent prognostic factor in childhood acute lymphoblastic leukemia (ALL). The most widely applied MRD assays in ALL are flow cytometric identification of leukemia immunophenotypes and polymerase chain reaction (PCR) amplification of antigen-receptor genes. We measured MRD by both assays in 227 patients with childhood B-lineage ALL. Of 1375 samples (736 bone marrow and 639 peripheral blood) examined, MRD was o0.01% in 1200, and X0.01% in 129 by both assays; MRD levels m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
103
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 39 publications
13
103
1
1
Order By: Relevance
“…Nonetheless, even if the techniques used to detect MRD may vary, some authors have shown that MFC-and PCR-based detection methods in ALL provides concordant results in the vast majority of cases. 32 In our analysis, we confirmed that the presence of detectable MRD assessed either by PCR (n ¼ 119) or by MFC (n ¼ 51) was statistically associated with LFS (PCR: P ¼ 0.02, MFC: P ¼ 0.05) and relapse (PCR: P ¼ 0.04, MFC: P ¼ 0.01).…”
Section: Discussionsupporting
confidence: 76%
“…Nonetheless, even if the techniques used to detect MRD may vary, some authors have shown that MFC-and PCR-based detection methods in ALL provides concordant results in the vast majority of cases. 32 In our analysis, we confirmed that the presence of detectable MRD assessed either by PCR (n ¼ 119) or by MFC (n ¼ 51) was statistically associated with LFS (PCR: P ¼ 0.02, MFC: P ¼ 0.05) and relapse (PCR: P ¼ 0.04, MFC: P ¼ 0.01).…”
Section: Discussionsupporting
confidence: 76%
“…Sensitivity can be determined exactly for every junctional region target and currently tends to be 0.5-1.0 log higher than while using flow cytometric MRD assessment. [48][49][50] However, a main disadvantage of using Ig/TCR gene rearrangements as MRD targets in ALL is the occurrence of continuing rearrangements during the disease course, potentially leading to false-negative PCR results. 46,[51][52][53] Moreover, follow-up of subclones existing at initial diagnosis may lead to overestimation or underestimation of MRD values.…”
Section: Pcr Analysis Of Ig and Tcr Gene Rearrangementsmentioning
confidence: 99%
“…20,[48][49][50]57 Instead, FCM-based risk definition may be independently reliable and therefore has to be independently validated.…”
Section: Multiparameter Fcmmentioning
confidence: 99%
“…Moreover, they published recently a large-scale comparative analysis on flow cytometry and PCR for the detection of MRD, showing good concordance and recommending a tandem application. 4 In Europe, molecular genetics is most widely used in a number of countries for MRDquantification in ALL, and a co-operative group has been established to set standards for quality control in the different laboratories. This is essential if a method is being applied in several institutions or reference laboratories in order to get reliable and comparable results.…”
Section: To the Editormentioning
confidence: 99%